Marital Property as Debt Collateral without Spousal Consent in Indonesia: Legal Validity, Execution, and Judicial Interpretation - Mhd. Yadi harahap; Sri Turatmiyah; Mhd Syahdani harahap (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2025)
One of the issues frequently debated in family law concerns the legal status of marital property. Conceptually, property acquired during marriage constitutes marital property unless otherwise stipulated in a prenuptial or postnuptial agreement. Legal problems arise when marital property is used as collateral for debt without the consent of one spouse, particularly with regard to the validity of such collateralization, the enforceability of its execution, and the settlement of marital property execution in the event of divorce.This study aims to analyze the legal status and execution of marital property pledged as collateral for debt without spousal consent, with reference to Supreme Court Decision Number 209 K/PDT/2000. This research employs a normative juridical method using a statute approach and a case approach. The findings indicate that marital property used as collateral for debt without the consent of both spouses lacks legal validity and cannot be lawfully executed by creditors, as such actions violate the principle of joint ownership and involve third-party interests. The Supreme Court decision affirms that neither spouse may unilaterally perform legal acts over marital property for the purpose of debt settlement through execution. This study contributes to the development of family and property law by clarifying the legal consequences of unauthorized collateralization of marital property and by reinforcing the principle of joint ownership protection. The findings are expected to provide normative guidance for courts and creditors, while also encouraging regulatory reform to ensure legal certainty and fairness for all parties.